Implementation of Discovery Learning Model Based on Calor Characteristic Bricks Mixed by (Durio Zibethinus) and Coconut (Cocos Nucifera) Skin to Improve Students’ Cognitive Learning Outcomes - Mayub, A.; Suryani, E.; Farid, M. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2020)
This study aims to determine the cognitive learning outcomes of students through learning the Discovery Learning model that uses practicum material bricks mixed by durian and coconut skin. The briquettes were implemented as practicum materials on temperature and heat learning in the Discovery Learning model to improve learning outcomes of KIR students in SMP N 15 Kota Bengkulu. Bomb Calorimeter in Chemical Laboratory Basic Science UNIB was used to determine the calorific value of briquette variations in the mixture of durian and coconut shell skin. The characteristics of briquette were carried out in the Science Laboratory. The instrument used in learning implementation was a multiple-choice test form that has been validated. Result of learning implementation showed that students’ cognitive learning outcomes increased after Discovery Learning model was implemented. The N-gain value was 0.78 in the high group, 0.57 in the medium group, and 0.53 in the low group.